Influencing Factors of Sedentary Behavior in European Preschool Settings: An Exploration Through Focus Groups With Teachers. (23rd July 2013) - De Decker, Ellen; De Craemer, Marieke; De Bourdeaudhuij, Ilse; Wijndaele, Katrien; Duvinage, Kristin; Androutsos, Odysseas; Iotova, Violeta; Lateva, Mina; Alvira, Juan Miguel Fernández; Zych, Kamila; Manios, Yannis; Cardon, Greet
ABSTRACT: BACKGROUND: Sedentary behavior refers to activities involving sitting down and reclining (eg, watching TV, using the computer) and has been associated with different health outcomes. In preschool, children are sedentary for 50% to 80% of the time, in the classroom as well as during recess. Because of the absence of qualitative studies examining influencing factors of preschoolers' sedentary behavior in preschool settings, this study explored teachers' opinions on potentially influencing factors of this behavior. METHODS: Eighty‐seven teachers of 4‐ to 6‐year‐old preschoolers from 6 European countries participated in a total of 18 focus groups between October 2010 and January 2011. Key findings were reported separately by country, and were independently analyzed by 2 researchers using qualitative content analysis. RESULTS: Teachers perceive the lack of play space and small classroom size as being influential factors on preschoolers' sedentary behavior; increasing play equipment and using teachers' prompts are mentioned as ways to stimulate children to be less sedentary on the playground. Computer use is reported to be more common in preschool than watching TV. CONCLUSION: Interventions should focus on increasing teachers' awareness of how sedentary preschoolers are during the preschool day. Teachers also should be informed about strategies to decrease sedentariness in the classroom and on the playground.